THE GLUEBALL SPECTRUM AND SCALING IN SU(3) LATTICE GAUGE-THEORY - Michael, C; Teper, M (1988)
We calculate glueball masses and the string tension on lattices as large as 204 and at couplings as small as β= 6 g2=6.2. To be able to do so we construct wave-functionals that maintain a good overlap with the long-distance physics as the lattice spacing is made small. Our calculations strongly indicate that the lightest glueball is the 0++ and that the next highest levels are a nearly degenerate 2++ and 0-+ at roughly 1.6m[0++]. In addition there is a 1+- just below 2m[0++]. The mass of the scalar is about 3.5 times the square root of the string tension. We find that this ratio is consistent with being independent of β for β≥5.9 (in contrast to its strong variation at lower β) and that this appears tobe so at a statistically significant level. The ratio of the 2++ and 0++ glueball masses is also consistent with being independent of β. © 1988.